Biological, Neuroimaging, and Neurophysiological Markers in Frontotemporal Dementia: Three Faces of the Same Coin. - Borroni, Barbara; Benussi, Alberto; Premi, Enrico; Alberici, Antonella; Marcello, Elena; Gardoni, Fabrizio; Di Luca, Monica; Padovani, Alessandro (J Alzheimers Dis, 2018)
Frontotemporal dementia (FTD) is a heterogeneous clinical, genetic, and neuropathological disorder. Clinical diagnosis and prediction of neuropathological substrates are hampered by heterogeneous pictures. Diagnostic markers are key in clinical trials to differentiate FTD from other neurodegenerative dementias. In the same view, identifying the neuropathological hallmarks of the disease is key in light of future disease-modifying treatments. The aim of the present review is to unravel the progress in biomarker discovery, discussing the potential applications of available biological, imaging, and neurophysiological markers.

Looking for Measures of Disease Severity in the Frontotemporal Dementia Continuum. - Premi, Enrico; Gualeni, Vera; Costa, Paolo; Cosseddu, Maura; Gasparotti, Roberto; Padovani, Alessandro; Borroni, Barbara (J Alzheimers Dis, 2016)
Frontotemporal dementia (FTD) is characterized by executive dysfunctions, behavioral disturbances, language deficits and extrapyramidal symptoms. Frontotemporal lobar degeneration-modified Clinical Dementia Rating Scale (FTLD modified-CDR) has been proposed to measure disease severity in behavioral variant FTD (bvFTD). No tools of global disease severity are available in the other FTLD phenotypes [primary progressive aphasias (PPAs), progressive supranuclear palsy (PSP), and corticobasal syndrome (CBS)]. This would be strategic as outcome measures in clinical trials. To this aim, we evaluated the association between brain volume (voxel based morphometry) and available clinical scales in FTD. In 176 FTD patients (64 bvFTD, 40 PPAs, 32 PSP, 40 CBS), instrumental activities of daily living (ADLs), FTLD-modified CDR, Mini-Mental State Examination (MMSE), Frontal Behavioral Inventory (FBI), and Neuropsychiatry Inventory (NPI) were administered and MRI performed. Whole-brain linear correlation between each clinical rating scale and brain volume was performed. In bvFTD and PPAs, FTLD-modified CDR was associated with regional brain volume, thereby providing evidence for validity of the FTLD-modified CDR. In PSP, none of the clinical indicators were associated with regional brain volume. In CBS, ADLs and MMSE correlated with frontotemporal lower volume. Considering monogenic disease, FTLD-modified CDR was the best measure. In FTD continuum, different measures able to correlate with brain damage should be considered for the different clinical phenotypes or genetic traits.

Looking for Neuroimaging Markers in Frontotemporal Lobar Degeneration Clinical Trials: A Multi-Voxel Pattern Analysis Study in Granulin Disease. - Premi, Enrico; Cauda, Franco; Costa, Tommaso; Diano, Matteo; Gazzina, Stefano; Gualeni, Vera; Alberici, Antonella; Archetti, Silvana; Magoni, Mauro; Gasparotti, Roberto; Padovani, Alessandro; Borroni, Barbara (J Alzheimers Dis, 2016)
In light of future pharmacological interventions, neuroimaging markers able to assess the response to treatment would be crucial. In Granulin (GRN) disease, preclinical data will prompt pharmacological trials in the future. Two main points need to be assessed: (1) to identify target regions in different disease stages and (2) to determine the most accurate functional and structural neuroimaging index to be used. To this aim, we have taken advantage of the multivariate approach of multi-voxel pattern analysis (MVPA) to explore the information of brain activity patterns in a cohort of GRN Thr272fs carriers at different disease stages (14 frontotemporal dementia (FTD) patients and 17 asymptomatic carriers) and a group of 33 healthy controls. We studied structural changes by voxel-based morphometry (VBM), functional connectivity by assessing salience, default mode, fronto-parietal, dorsal attentional, executive networks, and local connectivity by regional homogeneity, amplitude of low frequency fluctuations (ALFF), fractional ALFF (fALFF), degree centrality, and voxel-mirrored homotopic connectivity. In FTD patients with GRN mutation, the most predictive measure was VBM structural analysis, while in asymptomatic carriers the best predictor marker was the local connectivity measure (fALFF). Altogether, all indexes demonstrated fronto-temporo-parietal damage in GRN pathology, with widespread structural damage of fronto-parietal and temporal regions when disease is overt. MVPA could be of aid in identifying the most accurate neuroimaging marker for clinical trials. This approach was able to identify both the target region and the best neuroimaging approach, which would be specific in the different disease stages. Further studies are needed to simultaneously integrate multimodal indexes in a classifier able to trace the disease progression moving from preclinical to clinical stage of the disease.
Keywords: Adult; Aged; Brain; Brain Mapping; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Humans; Image Processing, Computer-Assisted; Intercellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Neural Pathways; Oxygen; Phenylalanine; Threonine

Vascular Risk Factors and Cognition in Parkinson's Disease. - Pilotto, Andrea; Turrone, Rosanna; Liepelt-Scarfone, Inga; Bianchi, Marta; Poli, Loris; Borroni, Barbara; Alberici, Antonella; Premi, Enrico; Formenti, Anna; Bigni, Barbara; Cosseddu, Maura; Cottini, Elisabetta; et al. (J Alzheimers Dis, 2016)
Vascular risk factors have been associated with cognitive deficits and incident dementia in the general population, but their role on cognitive dysfunction in Parkinson's disease (PD) is still unclear. The present study addresses the single and cumulative effect of vascular risk factors on cognition in PD patients, taking clinical confounders into account. Standardized neuropsychological assessment was performed in 238 consecutive PD patients. We evaluated the association of single and cumulative vascular risk factors (smoking, diabetes, hypercholesterolemia, hypertension, and heart disease), with the diagnosis of PD normal cognition (PDNC, n = 94), mild cognitive impairment (PD-MCI, n = 111), and dementia (PDD, n = 33). The association between single neuropsychological tests and vascular risk factors was evaluated with covariance analyses adjusted for age at onset, educational levels, gender, disease duration, and motor performance. Age, educational levels, disease duration, and motor function were significantly different between PDNC, PD-MCI, and PDD. Heart disease was the only vascular factor significantly more prevalent in PDD compared with PDNC in adjusted analyses. Performance of tests assessing executive and attention functions were significantly worse in patients with hypertension, heart disease, and/or diabetes (p <  0.05). Heart disease is associated with dementia in PD, suggesting a potential window of intervention. Vascular risk factors act especially on attention and executive functions in PD. Vascular risk stratification may be useful in order to identify PD patients with a greater risk of developing dementia. These findings need to be verified in longitudinal studies.
Keywords: Age of Onset; Aged; Attention; Disability Evaluation; Educational Status; Executive Function; Female; Humans; Male; Motor Activity; Neuropsychological Tests; Parkinson Disease; Prevalence; Risk Factors; Sex Factors; Time Factors; Vascular Diseases